Strategi Manajemen Sumber Daya Manusia dalam Meningkatkan Kompetensi Pendidik - Feri Fauzi Firdaus (CV. Biha Cendekia, 2025)
This study aims to analyze the role of human resource management (HRM) in improving the quality and skills of educators in educational institutions, especially at the Al-Fattah Community Learning Center (PKBM) Manonjaya, Tasikmalaya Regency. The research approach used is qualitative with a case study design. Data were collected through in-depth interviews with the head of PKBM, tutors, and education personnel, direct observation of the learning process and HR management, and supporting documentation. The results showed that HR management practices that include strategic planning, competency-based recruitment, continuous training, and structured performance evaluation have a positive impact on improving educators' competence. Effective implementation of HRM is able to create educators and education personnel who are more adaptive, professional and responsive to educational challenges in the digital era. This study concludes that comprehensive and integrated HR management is a key factor in improving the quality of non-formal education institutions.